2016
DOI: 10.1124/dmd.116.069906
|View full text |Cite
|
Sign up to set email alerts
|

The Absolute Bioavailability and Effect of Food on the Pharmacokinetics of Odanacatib: A Stable-Label i.v./Oral Study in Healthy Postmenopausal Women

Abstract: A stable-label i.v./oral study design was conducted to investigate the pharmacokinetics (PK) of odanacatib. Healthy, postmenopausal women received oral doses of unlabeled odanacatib administered simultaneously with a reference of 1 mg i.v. stable 13 C-labeled odanacatib. The absolute bioavailability of odanacatib was 30% at 50 mg (the phase 3 dose) and 70% at 10 mg, which is consistent with solubility-limited absorption. Odanacatib exposure (area under the curve from zero to infinity) increased by 15% and 63% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…Based on data from a phase 2b dose-ranging study, dosedependent increases in bone mineral density (BMD) at the lumbar spine and hip sites have been observed with once-weekly administration of ODN at doses ranging from 10 to 50 mg. 1-3 ODN has been evaluated in different populations, including Japanese subjects in a separate dose-ranging phase 2b study, 4 which also demonstrated dose-dependent increases in BMD and further supported the selection of the 50-mg dose for the global phase 3 Long-term Odanacatib Fracture Trial (LOFT; NCT00529373). 6 The pharmacokinetics (PK) and pharmacodynamics of ODN have been characterized in phase 1 single-dose 7 and multiple-dose 8,9 studies conducted in healthy men and postmenopausal women. 5 ODN is a Biopharmaceutics Classification System class II drug with high permeability (consistent with absorption via passive diffusion) and low solubility (below 0.001 mg/mL in water).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on data from a phase 2b dose-ranging study, dosedependent increases in bone mineral density (BMD) at the lumbar spine and hip sites have been observed with once-weekly administration of ODN at doses ranging from 10 to 50 mg. 1-3 ODN has been evaluated in different populations, including Japanese subjects in a separate dose-ranging phase 2b study, 4 which also demonstrated dose-dependent increases in BMD and further supported the selection of the 50-mg dose for the global phase 3 Long-term Odanacatib Fracture Trial (LOFT; NCT00529373). 6 The pharmacokinetics (PK) and pharmacodynamics of ODN have been characterized in phase 1 single-dose 7 and multiple-dose 8,9 studies conducted in healthy men and postmenopausal women. 5 ODN is a Biopharmaceutics Classification System class II drug with high permeability (consistent with absorption via passive diffusion) and low solubility (below 0.001 mg/mL in water).…”
mentioning
confidence: 99%
“…5 ODN is a Biopharmaceutics Classification System class II drug with high permeability (consistent with absorption via passive diffusion) and low solubility (below 0.001 mg/mL in water). 6 The pharmacokinetics (PK) and pharmacodynamics of ODN have been characterized in phase 1 single-dose 7 and multiple-dose 8,9 studies conducted in healthy men and postmenopausal women. The absorption, distribution, metabolism, and excretion of ODN were investigated in both animals 10 and humans.…”
mentioning
confidence: 99%
“…The odanacatib pharmacokinetic (PK) profile was qualitatively similar throughout Phase 1 development including in PMW and older men who are more representative of populations in which osteoporosis is prevalent . Following 3 weeks of 50 mg once weekly dosing in healthy subjects, the geometric mean steady state area under the curve from 0 to 168 hours (AUC 0‐168 ) was 41.1 μM h, maximum plasma concentration was 393 nM, concentration at 168 hours was 126 nM and the harmonic mean apparent terminal half‐life was 84.8 hours .…”
Section: Introductionmentioning
confidence: 94%
“…Based on previous study data, the supratherapeutic dosing regimen selected was 300 mg of odanacatib on day 1 followed by 25 mg once daily on days 2 through 21, all administered with a high‐fat meal to augment exposure. This regimen was chosen in an attempt to provide odanacatib exposures in excess of those achieved in the clinical program to date . Following review of data in the supratherapeutic safety study, a similar regimen was chosen with a shorter duration for the thorough QTc study (300 mg of odanacatib on day 1 followed by 25 mg once daily for 3 days).…”
mentioning
confidence: 99%
“…This regimen was chosen in an attempt to provide odanacatib exposures in excess of those achieved in the clinical program to date. 11 Following review of data in the supratherapeutic safety study, a similar regimen was chosen with a shorter duration for the thorough QTc study (300 mg of odanacatib on day 1 followed by 25 mg once daily for 3 days).…”
mentioning
confidence: 99%